2016
DOI: 10.1021/acs.est.6b04845
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Changes Effect of Humic Acids on TiO2 Photocatalysis: From Inhibition to Mitigation of Electron–Hole Recombination

Abstract: A major challenge for photocatalytic water purification with TiO is the strong inhibitory effect of natural organic matter (NOM), which can scavenge photogenerated holes and radicals and occlude ROS generation sites upon adsorption. This study shows that phosphate counteracts the inhibitory effect of humic acids (HA) by decreasing HA adsorption and mitigating electron-hole recombination. As a measure of the inhibitory effect of HA, the ratios of first-order reaction rate constants between photocatalytic phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 49 publications
0
49
1
Order By: Relevance
“…Some studies have shown that HA is easily adsorbed on the surface of the catalyst, which hinders the absorption of light [18]. As a result, the removal ability of bromate reduced to a certain degree.…”
Section: Hamentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that HA is easily adsorbed on the surface of the catalyst, which hinders the absorption of light [18]. As a result, the removal ability of bromate reduced to a certain degree.…”
Section: Hamentioning
confidence: 99%
“…On the other hand, the formation of reactive species by the reaction of 3 HA * with dissolved oxygen make the IBP photolysis indirectly [22,23]. In addition, due to the competition for photons and reactive oxygen radicals between HA and IBP under high concentration of HA [18], the inhibition effect on IBP degradation enhances, thereby results a slight decrease in removal rate with the HA concentration increases from 5 to 10 mg/L.…”
Section: Hamentioning
confidence: 99%
“…Due to highly rigid demanding for various functional photocatalysts in environmental applications, TiO 2 stands as one of the most widely studied semiconductors and highlighted for heterogeneous photocatalysts [1][2][3]. By splitting water in solar energy conversion cells, it also serves as the promising candidate for photoanode material.…”
Section: Introductionmentioning
confidence: 99%
“…Many research works at lab-scale have been carried out to removal micropollutants from water using suspension of TiO2 fine particles [61,107,[141][142][143]. The use of suspension of TiO2 fine particles is beneficial for fundamental research at lab-scale but not favourable in real life implication.…”
Section: Other Processesmentioning
confidence: 99%
“…The application of TiO2 for pollutants elimination has received enormous research interests [110][111][112][113][114]. Many research works at lab-scale have been carried out on removal of micropollutants from water using suspension of TiO2 nanoparticles [61,107,[141][142][143]. The use of TiO2 nanoparticles is beneficial for fundamental research at lab-scale due to their high surface area which allows for good mass transfer, but not favourable in real life implications [151].…”
Section: Use Of Tio2 Nanotube Array As Immobilized Photocatalystmentioning
confidence: 99%